South African budget 2019 : hard choices in tough times - Schaling, Eric, 1962-; Hobbs, Jacklynne; Beswick, Claire (London : Wits Business School, 2019)
In January 2019, as South Africa's minister of finance, Tito Mboweni, was finalising the country's 2019 budget, the country's fiscal position remained on a knife-edge. On the positive side, the expenditure ceiling to which the government had committed itself in the 2018/19 budget remained intact. Nevertheless economic growth predictions remained low, the country's debt was reaching unsustainable levels and the perilous financial position of some of the country's state-owned entities (SOEs) was putting the entire fiscus in peril. Mboweni and his team had to find a way of putting the country on a path to fiscal sustainability, given the fiscal inheritance that his predecessors had left him.
Originally Published In Schaling, E., Hobbs, J., & Beswick, C. (2019). South African Budget 2019: Hard Choices in Tough Times. WBS-2019-01. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Mboweni, T. T; Budget -- South Africa; South Africa -- Appropriations and expenditures